Perceived utility and disutility of genomic sequencing for pediatric patients: Perspectives from parents with diverse sociodemographic characteristics. Issue 4 (3rd January 2022) - Halley, Meghan C.; Young, Jennifer L.; Fernandez, Liliana; Kohler, Jennefer N.; ,; Bernstein, Jonathan A.; Wheeler, Matthew T.; Tabor, Holly K.
Abstract: Given the limited therapeutic options for most rare diseases diagnosed through genomic sequencing (GS) and the proportion of patients who remain undiagnosed even after GS, it is important to characterize a broader range of benefits and potential harms of GS from the perspectives of families with diverse sociodemographic characteristics. We recruited parents of children enrolled in the Undiagnosed Diseases Network. Parents completed an in‐depth interview, and we conducted a comparative content analysis of the data. Parents ( n  = 30) were demographically diverse, with 43.3% identifying as Hispanic, 33.3% primarily Spanish‐speaking, and widely variable household income and education. Parents reported minimal changes in their child's health status following GS but did report a range of other forms of perceived utility, including improvements in their child's healthcare management and access, in their own psychological well‐being, and in disease‐specific social connections and research opportunities. Parents who received a diagnosis more frequently perceived utility across all domains; however, disutility also was reported by both those with and without a diagnosis. Impacts depended on multiple mediating factors, including parents' underlying expectations and beliefs, family sociodemographic characteristics, individual disease characteristics, and prior healthcare access. Our study suggests that the perceived utility of GS varies widely among parents and may depend on multiple individual, sociodemographic, and contextual factors that are relevant for pre‐ and post‐GS counseling, for value assessment of GS, and for policymaking related to access to new genomic technologies.